An Archaeological Analysis of the Temples of Greater Mesopotamia from the Beginning of the ‘Ubaid Period to the End of the Early Dynastic Period - Sheen, Alun (1982)
Thesis submitted to the Faculty of Oriental Studies for the Degree of Doctor of Philosophy in the University of Oxford. Wolfson College, Oxford. Trinity term. Volume 1-2.; Supervisor: P. R. S. Moorey; Available from The British Library, Document Supply Centre. Order No. D50122'84.